Impact of kaolin addition on properties of quartz ceramics - Khomenko, E.S.; Karasik, E.V.; Goleus, V.I. (Functional Materials, 2017)
This paper presents one of methods of the quartz ceramics technological and physical- and-mechanical properties improvement by introduction of kaolin additive to its composition. Additive was added to slip prepared of the scrap quartz tubes; additive amount made 5, 10 and 15 wt. %. This results in observed improvement of rheological-and-processing characteristics for all slips, of which major one is reduction of slip tendency for sedimentation. In addition, the introduction of additive enhances compression strength of burned quartz material due to formation of the closely packed structure as compared with material without additive, which results in the material compression strength increase from 51 to 72 MPa.